2016
DOI: 10.1007/s13238-016-0316-z
|View full text |Cite
|
Sign up to set email alerts
|

miR-10a inhibits cell proliferation and promotes cell apoptosis by targeting BCL6 in diffuse large B-cell lymphoma

Abstract: The BCL6 (B-Cell Lymphoma 6) gene is a proto-oncogene that is often expressed in diffuse large B-cell lymphomas (DLBCLs). BCL6 loss of function can kill DLBCL cells, demonstrating that BCL6 is necessary for the survival of DLBCL cells and could be a therapeutic target. In this study, we found that BCL6 protein levels were consistently upregulated in DLBCL tissues, whereas its mRNA levels varied randomly in tissues, suggesting that a post-transcriptional mechanism was involved in BCL6 regulation. We used bioinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…expression of miRNAs has been found in several cancers, which play novel roles as anti-oncogenes or oncogenes, depending on the function of the target genes. [15][16][17] Previous studies showed that aberrant expression of many miRNAs promote proliferation and metastases in GC. [18][19][20] However, the molecular events are not fully understood.…”
Section: Aberrantmentioning
confidence: 99%
See 1 more Smart Citation
“…expression of miRNAs has been found in several cancers, which play novel roles as anti-oncogenes or oncogenes, depending on the function of the target genes. [15][16][17] Previous studies showed that aberrant expression of many miRNAs promote proliferation and metastases in GC. [18][19][20] However, the molecular events are not fully understood.…”
Section: Aberrantmentioning
confidence: 99%
“…The biological functions of miRNAs that regulating gene expression include cell proliferation, cell apoptosis, stress tolerance, and fat metabolism . Aberrant expression of miRNAs has been found in several cancers, which play novel roles as anti‐oncogenes or oncogenes, depending on the function of the target genes . Previous studies showed that aberrant expression of many miRNAs promote proliferation and metastases in GC .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focused on the role of miR-10a, a downregulated miRNA in PCa, in regulating KDM4A and PCa progression. 20,21 MicroRNA profiling of 499 PCa tumor tissues and 52 normal tissues identified miR-10a as the most significant downregulated miRNA in PCa tumor F I G U R E 3 MiR-10a negatively regulated KDM4A in PCa cells. Hypermethylation of CpG islands of miR-10a led to decrease of miR-10a expression and was observed in gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Assays to quantify mature miRNAs were performed using TaqMan miRNA probes (Applied Biosystems, Foster City, CA, USA) according to the manufacturer's instructions. Quantitative RT-PCR was performed to quantify miRNA levels and mRNA levels (see our previous study for details [15]). The primers for PCR amplifications were as follows: KRAS (sense) 5'-GACTCTGAAGATGTACCTATGGTCCTA-3'; KRAS (antisense) 5'-CATCATCAACACCCTGTCTTGTC-3';GAPDH (sense) 5'-GATATTGTTGCCATCAATGAC-3';GAPDH (antisense) 5'-TTGATTTTGGAGGGATCTCG-3'.…”
Section: Methodsmentioning
confidence: 99%